2011
DOI: 10.1159/000329239
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis and Acute Kidney Injury Are Bidirectional

Abstract: Sepsis is the most common cause of acute kidney injury (AKI). There has been a growing body of evidence demonstrating the association between worsening of kidney function during sepsis and the risk of short- and long-term mortality. AKI in sepsis is associated with poor outcome and independently predicts increased mortality. Sepsis-associated AKI may therefore serve as a biomarker of adverse physiological events that portends worse outcome. Conversely, the important role of sepsis among intensive care unit pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…First, AKI is frequently complicated by altered immune function, increased propensity to infection, bleeding, and thrombosis. 25,26 Second, AKI can result in acute volume overload, acidemia, and hyperkalemia contributing to increased cardiac stress and risk of arrhythmias. 27 Third, crosstalk between the kidney and other organs involving inflammatory and proapoptotic pathways may result in multiorgan failure eventually causing death.…”
Section: Discussionmentioning
confidence: 99%
“…First, AKI is frequently complicated by altered immune function, increased propensity to infection, bleeding, and thrombosis. 25,26 Second, AKI can result in acute volume overload, acidemia, and hyperkalemia contributing to increased cardiac stress and risk of arrhythmias. 27 Third, crosstalk between the kidney and other organs involving inflammatory and proapoptotic pathways may result in multiorgan failure eventually causing death.…”
Section: Discussionmentioning
confidence: 99%
“…89,90 In AKI, the mortality rates remained high due to paucity in the sensitive and specific biomarkers of renal cell injury. 89,91 However, recently developed techniques have identified the two sensitive and specific biomarkers for early AKI, namely, kidney injury molecule 1 (KIM-1) and neutrophil gelatinase-associated lipocalin (NGAL). 92,93 It has been reported that the sensitivity for NGAL to predict AKI is 0.815.…”
Section: Discussionmentioning
confidence: 99%
“…In kidneys, sepsis induces acute injury, tissue damage, and decrease of renal function, diminishing the efficacy of fluid supplementation and other therapeutics (Matejovic et al, 2011;Zarjou and Agarwal, 2011;Mayeux and MacMillan-Crow, 2012). Development of new drugs to treat septic acute kidney injury (AKI) therefore has a great potential to reduce mortality and morbidity in patients (Bagshaw et al, 2009;Zarjou and Agarwal, 2011).…”
Section: Introductionmentioning
confidence: 99%